4
$\begingroup$

I am trying to evaluate the following summation : $\sum_{m=2}^{\infty}\sum_{n=1}^{m-1}\frac{1}{(2m-1)(2n-1)(2m-2n)}$

The above summation is a partial sum of another double summation, $\sum_{m=1}^{\infty}\sum_{n=1}^{m-1}\frac{1}{mn(m-n)}$. This second summation is equal to 2$\zeta(3)$. Hence, the first summation is convergent.

If we manipulate the summation that is in question, it turns out to be equal to $\sum_{m=1}^{\infty}\frac{H_{2m-1}}{(2m+1)^2}$ where $H_k$ represents the $k^{th}$ Harmonic number.

$\endgroup$
4
$\begingroup$

Here an alternative way:

$$\sum_{m\geq 2}\sum_{n=1}^{m-1}\frac{1}{(2m-1)(2n-1)(2m-2n)}=\frac{1}{2}\sum_{T\geq 1}\sum_{S=0}^{T-1}\frac{1}{(2T+1)(2S+1)(T-S)} $$ equals $$ \frac{1}{2}\sum_{S\geq 0}\sum_{T>S}\frac{1}{(2T+1)(2S+1)(T-S)}=\frac{1}{2}\sum_{S\geq 0}\sum_{d\geq 1}\frac{1}{(2S+2d+1)(2S+1)d} $$ or $$ \frac{1}{2}\sum_{S\geq 0}\sum_{d\geq 1}\int_{0}^{1}\frac{x^{2S}}{2S+1}\cdot\frac{x^{2d}}{d}\,dx=\frac{1}{2}\int_{0}^{1}\frac{\text{arctanh}(x)}{x}\cdot\left(-\log(1-x^2)\right)\,dx $$ or $$ \frac{1}{4}\int_{0}^{1}\frac{\log^2(1+x)-\log^2(1-x)}{x}\,dx $$ where $$ \int_{0}^{1}\frac{\log^2(1-x)}{x}\,dx = \int_{0}^{1}\frac{\log^2(x)}{1-x}\,dx = 2\zeta(3) $$ and $$ \int_{0}^{1}\frac{\log^2(1+x)}{x}\,dx\stackrel{\text{IBP}}{=}-2\int_{0}^{1}\frac{\log(1+x)\log(x)}{1+x}\,dx $$ is easily solved as $\frac{1}{4}\zeta(3)$ via $\log(1+x)=\log(1-x)-2\text{arctanh}(x)$, $x\mapsto\frac{1-x}{1+x}$ and

$$ \int_{0}^{1}\frac{\text{arctanh}(x)^k}{x}\,dx =\int_{0}^{+\infty}\frac{2t^k}{\sinh(2t)}\,dt=\frac{2k!}{2^k}\sum_{n\geq 0}\frac{1}{(2n+1)^{k+1}}=\frac{2k!}{2^k}\zeta(k+1)\left(1-\frac{1}{2^{k+1}}\right).$$

$\endgroup$
2
$\begingroup$

$$\small\sum_{m\geq 1}\frac{H_{2m-1}}{(2m+1)^2}=\sum_{m\geq 1}\frac{H_{2m}}{(2m+1)^2}-\sum_{m=1}^{+\infty}\frac{1}{2m(2m+1)^2}\stackrel{\text{PFD}}{=}\sum_{m\geq 1}\frac{H_{2m}}{(2m+1)^2}-\left(2-\frac{\pi^2}{8}-\log 2\right) $$ and in a similar way $$ \sum_{m\geq 1}\frac{H_{2m-1}}{(2m+1)^2}=\sum_{m\geq 1}\frac{H_{2m+1}}{(2m+1)^2}-\left(1-\frac{\pi^2}{8}-\log 2+\frac{7}{8}\zeta(3)\right). $$ The idea now is to evaluate $\sum_{m\geq 1}\frac{H_{2m+1}}{(2m+1)^2}$ from $\sum_{n\geq 1}\frac{H_n}{n^2}z^n$. Since $$ \sum_{n\geq 1}\frac{H_n}{n}z^n = \frac{1}{2}\log^2(1-x)+\text{Li}_2(x) $$ we have $$ \sum_{n\geq 1}\frac{H_n}{n^2}=\int_{0}^{1}\left(\frac{1}{2}\log^2(1-x)+\text{Li}_2(x)\right)\frac{dx}{x}=2\zeta(3) $$ $$ \sum_{n\geq 1}(-1)^n\frac{H_n}{n^2}=\int_{0}^{1}\left(\frac{1}{2}\log^2(1+x)+\text{Li}_2(-x)\right)\frac{dx}{x}=-\frac{5}{8}\zeta(3) $$ so $$ \sum_{k\geq 0}\frac{H_{2k+1}}{(2k+1)^2}=\frac{21}{16}\zeta(3) $$ and $$ \sum_{m\geq 1}\frac{H_{2m-1}}{(2m+1)^2} = \frac{7}{16}\zeta(3)-2+\frac{\pi^2}{8}+\log 2.$$ Anyway

$$\small \sum_{m=2}^{+\infty}\sum_{n=1}^{m-1}\frac{1}{(2m-1)(2n-1)(2m-2n)}=\sum_{m\geq 2}\frac{H_{2m-2}}{(2m-1)^2}=\sum_{m\geq 1}\frac{H_{2m}}{(2m+1)^2}=\color{red}{\frac{7}{16}\zeta(3)}. $$

$\endgroup$
2
$\begingroup$

Here is a shorter way. The double sum

$$s=\frac{1}{2} \sum _{m=2}^{\infty } \sum _{n=1}^{m-1} \frac{1}{(2 m-1) (2 n-1) (m-n)}\tag{1}$$

is easily done directly in integral form by using the generating function, writing

$$s = \int_{[0,1]^3}g(x,y,z) \,dx\,dy\,dz\tag{2}$$

where

$$g(x,y,z)=\frac{1}{2} \sum _{m=2}^{\infty } \sum _{n=1}^{m-1} y^{2 m-2} z^{2 n-2} x^{m-n-1}\\ =\frac{y^2}{2 \left(x y^2-1\right) \left(y^2 z^2-1\right)}\tag{3}$$

and then doing the triple integral step by step

$$g_x = \int_0^1 g \,dx = \frac{\log \left(1-y^2\right)}{2 y^2 z^2-2}\tag{4a}$$

$$g_{xz} = \int_0^1 g_x \,dz=-\frac{\log \left(1-y^2\right) \tanh ^{-1}(y)}{2 y}\\= \frac{\log ^2(1-y)-\log ^2(y+1)}{4 y} \tag{4b}$$

and finally

$$s=\int_0^1 \frac{\log ^2(1-y)-\log ^2(y+1)}{4 y} \, dy= \frac{7 \zeta (3)}{16}\tag{4c}$$

Discussion

§1. The order of integration was a lucky choice. If I would have tried the $y$-integration second that would have resulted in a complicated expression with derivatives of hypergeometric functions, and I surely would have given up instead if trying the remaining $z$-integration.

§2. A variation

For the sum with $(n-m)$ replaced by $(n+m)$ the same method takes us on a long journey through complicated structures but in the end the result is surprisingly simple:

$$s_{+}=\frac{1}{2} \sum _{m=2}^{\infty } \sum _{n=1}^{m-1} \frac{1}{(2 m-1) (2 n-1) (m+n)}\\ =\frac{3 \log (2)}{4}-\frac{\pi ^2}{32} \simeq 0.211435\tag{5}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.